All about outcomes an educational program to help you understand, evaluate, and choose adult outcome measures - Law, Mary C.; Slack Incorporated (Thorofare, NJ : SLACK, Inc., 2001)
A self-directed multimedia software program for practitioners working in rehabilitation with adults and seniors. This CD-ROM enables the user to select the most beneficial outcome measure to use for an individual, client, service, and/or program evaluation. It guides the user through a protocol for making decisions about outcomes developed using a modified version of the International Classification of Impairment, Disability and Handicap (ICIDH) framework.
System requirements: 486 or Pentium-based PC; Windows 95 or later; 8 MB of RAM (16 MB preferred); 15 MB of hard disk storage; 1 MB (or higher) SVGA video card; CD-ROM drive
Keywords: Outcome assessment (Health care); Rehabilitation -- Adult; Rehabilitation -- Aged; Decision Making, Computer-Assisted